Altered Subpopulations of Red Blood Cells and Post-treatment Anemia in Malaria - Chambrion, Charlotte; Depond, Mallorie; Angella, Lucia; Mouri, Oussama; Kendjo, Eric; Fricot-Monsinjon, Aurélie; Roussel, Camille; Biligui, Sylvestre; Tantaoui, Ilhame; Taieb, Aida; Argy, Nicolas; Houzé, Sandrine; et al. (Frontiers in Physiology, 2022)
In acute malaria, the bulk of erythrocyte loss occurs after therapy, with a nadir of hemoglobin generally observed 3-to 7 days after treatment. The fine mechanisms leading to this early post-treatment anemia are still elusive. We explored pathological changes in RBC subpopulations by quantifying biochemical and mechanical alterations during severe malaria treated with artemisinin derivatives that induce “pitting” in the spleen. In this study, the hemoglobin concentration dropped by 1.85 G/dL during therapy. During the same period, iRBC accounting for 5.9% of all RBC before therapy (BT) were replaced by pitted-RBC, accounting for 5.1% of RBC after therapy (AT). RBC loss was thus of 14.4 %, of which only a minor part was due to the loss of iRBC or pitted-RBC. When comparing RBC BT and AT to normal controls, lipidomics revealed increase in the cholesterol/phosphatidylethanolamine ratio (0.17 versus 0.24, p<0.001) and cholesterol/phosphatidylinositol ratio (0.36 versus 0.67, p= 0.001). Using ektacytometry, we observed a reduced deformability of circulating RBC to a similar extend BT and AT, compared to health control donors. The mean Elongation Index at 1.69Pa was 0.24Pa BT and 0.23Pa AT vs. 0.28Pa in controls (p <0.001). At 30Pa EI was 0.56Pa BT and 0.56Pa AT vs. 0.60Pa in controls (p <0.001). The retention rate (rr) of RBC subpopulations in spleen-mimetic microsphere layers was higher for iRBC (rr= 20% p< 001) and pitted-RBC (rr= 19%, p= 0.003) than for healthy RBC (0.12%). Somewhat surprisingly, the initial anemia results from the elimination of RBC that were never infected.